Observations on an epilobic Lumbricus rubellus (Oligochaeta, Lumbricidae) from the Great Smoky Mountains National Park, Tennessee, USA - Carrera-Martínez, Roberto; Callaham, Mac A. Jr. (Zootaxa, 2018)
The genus Lumbricus L. was the first described genus of earthworms, with L. terrestris as its type species. The genus can be easily distinguished because it is the only lumbricid genus with a tanylobic prostomium, with the exception of the North American native Bimastos eiseni (Levinsen). With six known Lumbricus species introduced in North America (Reynolds & Wetzel, 2012), Lumbricus rubellus is one of the most widespread. In addition, L. rubellus has been associated with negative ecological effects as result of its invasion (Greiner et al. 2012). The Great Smoky Mountains National Park in Tennessee and North Carolina, USA, is no exception from earthworm invasions (Snyder et al. 2011). Recent research in an area near the extreme southwestern end of the Park (35.5538º N; 83.9943º W), resulted in the collection of ten specimens of L. rubellus, on 27 July 2011. Among these specimens was one that had an abnormal epilobic prostomium and under-developed tubercula pubertatis, whereas the rest had the typical Lumbricus tanylobic prostomia and fully developed tubercula pubertatis. To facilitate discrimination and identification in future encounters of an epilobic L. rubellus we provide here a full description of this specimen. To our knowledge, this is the first reported case of a specimen of L. rubellus with an epilobic prostomium. The specimen will be deposited in the nascent Terrestrial Oligochaete Collection at the Georgia Museum of Natural History in Athens, Georgia, USA. The specimen was fixed in 10% formalin, and is preserved in 70% ethanol.